2018
DOI: 10.1590/1807-1929/agriambi.v22n11p747-752
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation with mycorrhizal fungi on the growth and tolerance to water deficit of coffee plants

Abstract: Water stress can be alleviated in plants inoculated with arbuscular mycorrhizal fungi compared to that experienced by those without mycorrhizae. The objective of this study was to evaluate the growth of coffee plants colonized by arbuscular mycorrhizal fungi under different soil moisture conditions. Seeds of the coffee cultivar Catuaí Vermelho IAC 99 and three fungal inoculants (Rhizophagus clarus, Claroideoglomus etunicatum and Dentiscutata heterogama) were used in this study. The soil moisture contents teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
(20 reference statements)
0
6
0
1
Order By: Relevance
“…The relative growth rate of coffee is higher in FC than in WD (Cavatte et al, 2012). The coffee tree growth decreased as the soil water availability reduced (Moreira et al, 2018), and both the vegetative and reproductive stages were affected by WD (Aparecido & Rolim, 2018). Normally, plant growth under water stress is reduced due to its decrease in photosynthetic rate (Liu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The relative growth rate of coffee is higher in FC than in WD (Cavatte et al, 2012). The coffee tree growth decreased as the soil water availability reduced (Moreira et al, 2018), and both the vegetative and reproductive stages were affected by WD (Aparecido & Rolim, 2018). Normally, plant growth under water stress is reduced due to its decrease in photosynthetic rate (Liu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…According to Bahrun et al (2018), most small farmers grow cocoa seedlings in polybags filled with unsterilized. Adaptation to poor soil fertility and water deficit conditions of cocoa seedlings can be further improved by the application of AMF spore inoculum (Moreira et al, 2018;Seutra Kaba et al, 2021). Azizah Chulan (1991), reported the inoculation of AMF spores (Scutellospora calospora) produced from a mixture of soil and infected root pieces significantly increased nutrient absorption and growth in cocoa seedlings grown in sterilized soil.…”
Section: Introductionmentioning
confidence: 99%
“…Arbuscular mycorrhizal fungi are obligate biotrophic symbionts of widespread occurrence in soils with coffee plantations (Arias et al 2012). Previous research has shown that coffee plants are extremely dependent on such symbiosis (Saggin Júnior and Siqueira 1996), which increases their tolerance to fungal pathogens, nematodes (Alban et al 2013), water deficit (Moreira et al 2018) and weeds (França et al 2016) and improves their intake of nutrients (Saggin Júnior et al 1994), especially phosphorus (Siqueira et al 1998). In addition to these direct benefits to coffee plants, AMF species play a role in soil structure through their extraradical hyphae and production of a protein in the mycorrhizal fungal cell walls, called glomalin (Carneiro et al 2015).…”
Section: Introductionmentioning
confidence: 99%